Relationship between anthropometry and cardiorespiratory fitness among UiTM football players / Noor Fatihah Ilias, Siti Soraya Mohd Elias and Muhammad Alif Zulkifli - Ilias, Noor Fatihah; Mohd Elias, Siti Soraya; Zulkifli, Muhammad Alif (Universiti Teknologi MARA, 2023)
Cardiorespiratory fitness (CRF) is one of the important components among football players. Physiological characteristics of individuals such as anthropometry may influence the level of CRF. Therefore, this study aims to determine the relationship between anthropometry and CRF among UiTM Football Players. A causal- comparative research design, consisting of 24 male participants representing Universiti Teknologi MARA Football Club (UiTM FC) were recruited. Anthropometry was measured via body weight and body height and CRF was measured using a bleep test and the result of the test was calculated to estimate maximum volume of oxygen (VO2 max). Pearson correlation was used to determine the relationship between anthropometry and CRF. Mean score for anthropometry was 65.17 ± 5.90 for bodyweight (kg) and 171.18 ± 4.66 for body height (cm). Mean score for CRF was 47.20 ± 4.34 (ml/kg/min). Results show a very weak relationship between body weight and CRF (r = 0.027). Meanwhile, there was a positive and weak relationship between body height and CRF (r =0.265). In conclusion, evidence from this study showed no association between anthropometry and cardiorespiratory fitness. However, possibly a good anthropometry characteristic possibly gives the advantage of having good cardiorespiratory fitness. Ideal body weight and height is a potential physiological characteristic in determinants of cardiorespiratory fitness. Anthropometric does have a role as part of holistic monitoring of talented players in future development. Viewing the limitations of this study, further studies involving larger sample size are needed to find actual association with this hypothesis.